2012
DOI: 10.1016/j.neuropsychologia.2012.05.032
|View full text |Cite
|
Sign up to set email alerts
|

Time course of spatial and feature selective attention for partly-occluded objects

Abstract: Attention selects objects/groups as the most fundamental units, and this may be achieved by an attention-spreading mechanism. Previous event-related potential (ERP) studies have found that attention-spreading is reflected by a decrease in the N1 spatial attention effect.The present study tested whether the electrophysiological attention effect is associated with the perception of object unity or amodal completion through the use of partly-occluded objects. ERPs were recorded in 14 participants who were require… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
20
2
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(28 citation statements)
references
References 54 publications
(45 reference statements)
5
20
2
1
Order By: Relevance
“…The N2 attention effect (300-350 ms) was shifted positively for connected objects in the easy condition. The present lack of N1 effect stands in contrast with our previous studies, which found attention-spreading effects in the N1 latency range (Kasai, 2010;Kasai et al, 2011;Kasai & Takeya, 2012;Takeya & Kasai, 2014). The general stimulus configurations and tasks in the current study were similar to those in the previous studies; the critical difference was that unfilled line stimuli, rather than geometric shapes with filled surfaces, were used.…”
Section: Discussioncontrasting
confidence: 63%
See 4 more Smart Citations
“…The N2 attention effect (300-350 ms) was shifted positively for connected objects in the easy condition. The present lack of N1 effect stands in contrast with our previous studies, which found attention-spreading effects in the N1 latency range (Kasai, 2010;Kasai et al, 2011;Kasai & Takeya, 2012;Takeya & Kasai, 2014). The general stimulus configurations and tasks in the current study were similar to those in the previous studies; the critical difference was that unfilled line stimuli, rather than geometric shapes with filled surfaces, were used.…”
Section: Discussioncontrasting
confidence: 63%
“…However, it may be observed only when objects are clearly separated from each other. In our previous studies, the P2 attention effect may not have been found because filled objects can be grouped according to similarities in surface properties (Kasai, 2010;Kasai et al, 2011;Takeya & Kasai, 2014), whereas a P2 effect was observed when another object interrupted the grouping between bilateral stimuli (Kasai & Takeya, 2012). Luck et al (1990) also found a similar P2 attention effect for letters that were aligned in hemi-circles across the left and right hemi-fields, which raises the question of whether the existence of multiple elements within each field reduces grouping of bilateral stimuli.…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations